Efisiensi Bank Digital di Indonesia Menggunakan Data Envelopment Analysis (DEA) - Mikhael Garda Prasetya; Gideon Setyo Budiwitjaksono (IPM2KPE, 2023)
This study aims to determine the effect of Size, ROA, CAR, LDR and NPL on the efficiency of Digital Banks in Indonesia. The method used in this study is to use a quantitative method with the Two-Stage Data Envelopment Analysis (DEA) method. The data collection technique carried out by researchers in this study was through library research. The sample method used in this study is purposive sampling with 8 samples of digital banks in Indonesia for the 2018-2021 period. The results showed that the first phase of data analysis using DEA found that digital banks in Indonesia obtained an average efficiency score of 0.88 (high efficiency). The results of the tobit panel regression found that the Size and LDR variables had a significant positive effect on the efficiency of digital banks, Keywords: CAR, Bank Efficiency, LDR, NPL, ROA, Size